Herpes simplex virus 1 targets IRF7 via ICP0 to limit type I IFN induction - David Shahnazaryan (Nature Portfolio, 2020)
Abstract Herpes simplex keratitis (HSK), caused by herpes simplex virus type 1 (HSV-1) infection, is the commonest cause of infectious blindness in the developed world. Following infection the virus is initially suspended in the tear film, where it encounters a multi-pronged immune response comprising enzymes, complement, immunoglobulins and crucially, a range of anti-viral and pro-inflammatory cytokines. However, given that HSV-1 can overcome innate immune responses to establish lifelong latency throughout a susceptible individual’s lifetime, there is significant interest in understanding the mechanisms employed by HSV-1 to downregulate the anti-viral type I interferon (IFN) mediated immune responses. This study aimed to investigate the interactions between infected cell protein (ICP)0 and key elements of the IFN pathway to identify possible novel targets that contribute to viral immune evasion. Reporter gene assays demonstrated the ability of ICP0 to inhibit type I IFN activity downstream of pathogen recognition receptors (PRRs) which are known to be involved in host antiviral defences. Further experiments identified interferon regulatory factor (IRF)7, a driver of type I IFN, as a potential target for ICP0. These findings increase our understanding of the pathogenesis of HSK and suggest IRF7 as a potential therapeutic target.